Comparision of Latch Score Vs Breast Feeding Self Assessment Scale for Evaluating Breast Feeding Problems -A Prospective Observational Study - Teja R, Manne Sai; Prasad, K N Venkateshwara (Journal of Neonatal Surgery, 2025)
Background: Breastfeeding is vital for neonatal health, yet difficulties during early postpartum often hinder its successful establishment. Tools such as the Breastfeeding Self-Efficacy Scale-Short Form (BSES-SF) and the LATCH assessment are employed to evaluate maternal confidence and breastfeeding technique, respectively. However, comparative data on their effectiveness in clinical practice remains limited. Objective: To compare the BSES-SF and LATCH scores in identifying early breastfeeding problems and assess their feasibility and acceptability among healthcare providers. Methods: A prospective observational study was conducted from April 2023 to March 2024 at a tertiary care hospital in India. A total of 187 mothers with term neonates delivered via vaginal birth were included. Exclusion criteria comprised preterm births, NICU admissions, or need for intravenous fluids. BSES-SF and LATCH scores were recorded from <6 hours to Day 5 postpartum. Descriptive statistics, Pearson correlation, and significance testing (p < 0.05) were performed using SPSS v22. Results: Both BSES-SF and LATCH scores showed significant progressive increases over five days (BSES-SF: 31.78 ± 5.87 to 67.19 ± 2.57; LATCH: 4.52 ± 1.19 to 9.59 ± 0.51). However, no significant correlation was found between the two tools at any time point. Healthcare providers reported high usability for both tools, with BSES-SF being easier to apply, while LATCH was more time-efficient (<15 minutes in 59.4% of cases). Conclusion: Although BSES-SF and LATCH scores both improve with time postpartum, they assess different aspects of breastfeeding. Their lack of correlation suggests a complementary, rather than substitutive, role in clinical assessment. Integrating both tools may enhance early detection of breastfeeding difficulties and guide targeted interventions.